Model Aplikasi Pencarian Letak Rumah Sakit Terdekat Berbasis Android - Muhammad Haris Rahman; Taufiq Taufiq (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2015)
The limited information about the location of a hospital cause trouble for someone when they want to go to the hospital. The difficulty will be more so when the need to use these facilities is urgent. Newcomers and locals who want to go to the hospital often find it difficult to search the location of the hospital. This research will be made an application which can provide information about the hospital and the location of the nearest hospital from the user's position to be. Applications created consists of two parts, the application server and mobile applications. Application servers are used to process data management hospital. While the mobile application used to search the location of the nearest hospital. The algorithms used in the search process using the location nearest distance ratio is calculated from the comparison of the two points. Results information from the mobile application is a list of hospitals that have registered, detailed information from each hospital, hospital location map and information on the location of the nearest hospital to be the user's position.                                                                                                 Keywords: Application HospitalMap , Android